2020
DOI: 10.3390/technologies8030048
|View full text |Cite
|
Sign up to set email alerts
|

Hot Isostatic Pressing of Aluminum–Silicon Alloys Fabricated by Laser Powder-Bed Fusion

Abstract: Hot isostatic pressing can be utilized to reduce the anisotropic mechanical properties of Al–Si–Mg alloys fabricated by laser powder-bed fusion (L-PBF). The implementation of post processing densification processes can open up new fields of application by meeting high quality requirements defined by aircraft and automotive industries. A gas pressure of 75 MPa during hot isostatic pressing lowers the critical cooling rate required to achieve a supersaturated solid solution. Direct aging uses this pressure relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…In this scenario, Ertuğrul et al [ 107 ] also combined the HIP HT with the T6 to increase the mechanical properties, but the round Si particles become larger and more spherical, and the microstructure shows needle-like Fe-rich phases. The same results were reported by Schneller et al [ 108 ] and Hafenstein et al [ 167 ] who showed a decrease between 64 and 66% of the internal pores.…”
Section: L-pbfed Alsi10mg: Microstructuresupporting
confidence: 89%
See 1 more Smart Citation
“…In this scenario, Ertuğrul et al [ 107 ] also combined the HIP HT with the T6 to increase the mechanical properties, but the round Si particles become larger and more spherical, and the microstructure shows needle-like Fe-rich phases. The same results were reported by Schneller et al [ 108 ] and Hafenstein et al [ 167 ] who showed a decrease between 64 and 66% of the internal pores.…”
Section: L-pbfed Alsi10mg: Microstructuresupporting
confidence: 89%
“…In conclusion, the HIP HT, which can be used to reduce the internal pores inducing the sample’s densification, confers the same microstructural effects of the T6 HTs [ 107 , 108 , 167 ]. Merino et al [ 165 ] showed a complete recrystallization process after HIP (515 °C × 3 h × 100 MPa) and HIP + T6 (515 °C × 3 h × 100 MPa) + ((530 °C × 6 h) + (160 °C × 6 h)) HTs.…”
Section: L-pbfed Alsi10mg: Microstructurementioning
confidence: 99%
“…An error during the HIP meant that the target temperature (500 • C) was exceeded and a constant temperature of ∼570 • C was recorded over the 4 hrs of the HIP heating phase. This temperature is higher than commonly used for L-PBF aluminium 31 (510 • C to 540 • C) and, as such, the effect the aluminium micro-structure is unclear. Therefore, the role of HIP on surface roughness after SPDT requires further investigation.…”
Section: Resultsmentioning
confidence: 81%
“…Although this kind of porosity is commonly not considered detrimental to mechanical performance thanks to their small size and spherical shape, extreme applications, such as in the aerospace field, need to achieve a perfect densification of the component. To achieve this goal, tailored post-processing operations, such as hot isostatic pressing (HIP), need to be defined [ 87 ].…”
Section: During Processingmentioning
confidence: 99%